Kinetics of reduction of water to hydrogen by visible light on alumina supported Pt-CdS photocatalysts - Sahu N.; Upadhyay S.N.; Sinha A.S.K. (My University, 2025)
The kinetics of hydrogen production from photolysis of water on alumina supported Pt-CdS catalyst using visible light has been studied. An induction period with negligible rate was observed upon illumination of catalyst. The rate gradually increases and again falls down. The rate has been observed to be proportional to the sulfide ions adsorbed on the surface of CdS. The induction period has been related to the re-establishment of adsorption equilibrium of sulfide ions on the catalyst surface under illumination. The decrease in rate is due to the deactivation of catalyst by hydrogen. A power law type rate expression for hydrogen production has been proposed which takes into account the deactivation of the catalyst. © 2008 International Association for Hydrogen Energy.